Correlation between Trochlear Dysplasia and the Notch Index. (December 2013) - Botchu, Rajesh; Obaid, Haron; Rennie, WJ
Purpose: To evaluate the correlation between trochlear dysplasia and the notch index. Methods: Magnetic resonance images (MRI) of 95 knees in 54 male and 36 female patients aged 4 to 74 (mean, 28) years were reviewed by 2 musculoskeletal radiologists. Standard MRI sequences were used. Based on the Dejour classification of trochlear dysplasia, the knees were classified into normal or types A, B, C, and D. A notch index of <0.2 was considered narrow. Normal knees and knees with trochlear dysplasia were compared. Results: 60 of the 95 knees had trochlear dysplasia, of which 39 were Dejour type A, 13 were type B, 7 were type C, and one was type D. Dejour types B, C, and D were combined as non-type A. Inter-observer agreement in assessing the notch index was good (Kappa=0.6). The mean notch indices in normal knees and knees with trochlear dysplasia were comparable (0.161 vs. 0.157, p=0.18), as were in Dejour type A and non-type A knees (0.154 vs. 0.160, p=0.54) and in Dejour types A, B, C, and D knees (0.154 vs. 0.165 vs 0.153 vs. 0.2, p=0.17–0.7). The rate of ACL injuries was similar in patients with normal knees and those with type-A trochlear dysplasia. A low notch index (narrow notch) was not associated with ACL injury. Conclusion: The notch index and trochlear morphology are 2 independent entities. A narrow notch does not imply a shallow trochlear grove.